Evaluation and Application of TS-FF-AAS System Using Ceramic Tube as Atomization Cell for Tin Determination in Canned Foods - Lobo, Fabiana Aparecida [UNESP]; Villafranca, Ana Cristina [UNESP]; de Oliveira, Adriana Paiva; de Moraes, Mercedes [UNESP] (Perkin-elmer Corp, 2008)
Tinplate has been used for preserving food for well over a hundred years. Today it provides a robust form of packaging by allowing minimization of head-space oxygen and sterilization of the foodstuff within the hermetically sealed can. It also provides a long, safe, and ambient shelf life with no or minimal use of preservatives. However, the use of tinplate could result in contamination since some tin could dissolve into the food, particularly when plain uncoated internal surfaces are used. Monitoring this process is, therefore, very important to ensure quality standard and industrial control.This work describes the development of an analytical procedure for on-line tin determination by thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS) using a ceramic tube as an atomization cell in canned foods. Carrier flow rate (air), sample volume, and acid concentration (HCl) were evaluated for the optimization of the TS-FF-AAS system. An analytical linear curve was built [A= 0.0062 + 0.0069 (Sn), (r=0.9993)] in the 3.0-30 mg L-1 Sn range. The limit of detection, relative standard deviation (n=12, 1 mg L-1 Sn), and analytical frequency was: 0.8 mg L-1 Sn, <= 8.5% and 90 h(-1), respectively. Accuracy was checked by performing addition-recovery experiments. Recoveries varied from 95.0 to 104% for nine samples of the canned foods. According to a t-test, all results were compared statistically with values obtained by flame atomic absorption spectrometry (FAAS) using acetylene-nitrous oxide flame and were in agreement at the 95% confidence level.